Evaluasi Performa Keuangan PT Tunas Baru Lampung Tbk Menggunakan Rasio Keuangan - Sitorus, Maryana Enzelika; Arninda, Nevika (Asosiasi Dosen Akuntansi Indonesia, 2024)
PT Tunas Baru Lampung Tbk is a leading agribusiness company in Indonesia that focuses on producing and distributing palm oil. Analysis of financial statements is important for evaluating a company's financial performance and position in the context of external challenges and opportunities, such as the COVID-19 pandemic and commodity price fluctuations. The financial ratio analysis method evaluates a company's profitability, liquidity, solvency, activity, development, and productivity. This research adopts a quantitative descriptive approach by utilizing financial report data from PT Tunas Baru Lampung Tbk for 2020-2022. Financial ratio analysis shows improvements in several aspects of the company's financial performance despite facing certain fluctuations. PT Tunas Baru Lampung Tbk maintained relatively good financial health amidst external challenges, with efforts to increase operational efficiency and support long-term growth.